2007
DOI: 10.1002/adma.200602924
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Response of n‐Channel Naphthalenetetracarboxylic Diimide Transistors to Dimethyl Methylphosphonate Using Phenolic Receptors

Abstract: A bilayer organic field effect transistor (OFET) sensor utilizing a phenol functionalized molecule as a receptor layer, designed to enhance interaction with a target vapor dimethyl methylphosphonate (DMMP) is presented. The presence of this receptor layer is shown to enhance the sensing properties of the device, supporting the hypothesis that the phenolic receptor material is hydrogen bonding to the DMMP vapor molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…Yeon Taek Jeong, 1 Brian H. Cobb, 1 Shannon D. Lewis, 1 Ananth Dodabalapur, 1 We report on the realization of dual-channel organic field-effect transistors ͑FETs͒. These devices have a four-terminal configuration with a polymeric semiconductor p-channel, a small molecule semiconductor n-channel, and a polymeric gate dielectric.…”
Section: Realization Of Dual-channel Organic Field-effect Transistorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Yeon Taek Jeong, 1 Brian H. Cobb, 1 Shannon D. Lewis, 1 Ananth Dodabalapur, 1 We report on the realization of dual-channel organic field-effect transistors ͑FETs͒. These devices have a four-terminal configuration with a polymeric semiconductor p-channel, a small molecule semiconductor n-channel, and a polymeric gate dielectric.…”
Section: Realization Of Dual-channel Organic Field-effect Transistorsmentioning
confidence: 97%
“…[1][2][3][4][5] Conventional three-terminal OFET sensors are inherently operated in either OFET 3,4 or sensing gate FET ͑SGFET͒ modes. 6,7 In addition, the four-terminal geometry was successfully employed as a Si-organic hybrid dual-channel metal-oxide-semiconductor FET, with a coupled Si n-channel and organic p-channel.…”
Section: Realization Of Dual-channel Organic Field-effect Transistorsmentioning
confidence: 99%
“…OFET sensors can also work in water (19,20) as well as in the subvolt bias regime (20,21). Specificity relies on device structures that either involve enzymatic reactions [with FET electrochemical transduction (22)] or two-layer architectures, including a bioactive film deposited on top of the channel organic semiconductor (18,23,24). The reference electrode issue remains in electrochemical OFETs, while in the two-layer architecture the recognition event takes place far from the semiconductor/dielectric interface affecting the 2D electronic transport only indirectly (10).…”
mentioning
confidence: 99%
“…This interesting domain of research can be also considered as the most prominent imitation of nature that shows various examples emerging from co-operation between different constituents. [2] The concepts developed in supramolecular chemistry are increasingly employed in the field of advanced materials science such as optoelectronic devices, [3] sensor technology, [4] biological applications, [5] and nanotechnology. [6] croscopy of ultrathin layers of unsubstituted HBC 1a (5-8 molecules in thickness) on Cu(111) or Au(111) surfaces revealed that the columns are perfectly aligned with little translation.…”
Section: Introductionmentioning
confidence: 99%